Prevalence of Zoonotic and Other Intestinal Protozoan Parasites in Stray Cats (Felis domesticus) of Kerman, South-East of Iran - Sakineh BEIGI (İstanbul Üniversitesi Veteriner Fakültesi Dergisi, 2017)
Intestinal protozoan parasites constitute a major source of diseases for stray cats and have been recognized as important public health problems in several parts of the world. Considering the potential risk of stray cats for public health, present cross-sectional study was carried out to determine the type and frequency of protozoan parasites by faecal examination. A total of 100 stray cats were examined in Kerman city, Iran, Overall 67 cats (67%) were infected with at least one protozoan parasite. The following parasites, with their respective prevalence, were found; Isospora felis 38%, Isospora rivolta 25%, Toxoplasma gondii 16%, Sarcocystis spp. 8%, Cryptosporidium spp. 7%, and Giardia sp. 5%. Based on our data, the sex of stray cats was not significantly associated with the prevalence of gastrointestinal protozoan parasites. The high infection rate of zoonotic intestinal protozoan parasites in stray cats is considered to be critical from the viewpoint of public health importance.We